THE ROLE OF THE SEX TODAY BROADCAST PROGRAM AS A SEX EDUCATION MEDIA FOR TEENAGERS ON KARDOPA 99.4 FM MEDAN - Winda Kustiawan; Innayatilla; Rifqi Ramadhan Harahap; Zakiah Mahrani Harahap; Mahisa Agni; Ibnuburrahman; Putri Nadia Ritonga (Yayasan Amanah Nur Aman, 2026)
The increasing phenomenon of risky sexual behavior among adolescents is inextricably linked to limited access to structured and comprehensive sex education. This situation encourages adolescents to seek alternative sources of information through mass media, including radio. This study aims to analyze the role of the Sex Today broadcast program as a medium for sex education for adolescents on Kardopa 99.4 FM Medan, with an emphasis on the communication process, message meaning, and the dynamics of interaction between broadcasters and listeners. This study used a qualitative approach with data collection techniques including in-depth interviews, broadcast observations, and documentation. Informants were selected purposively based on their involvement and competence in program implementation. Data analysis was conducted using an interactive analysis model that includes data reduction, data presentation, and inductive conclusion drawing, and its validity was tested through triangulation of sources and techniques. The results show that Sex Today functions not only as a one-way message delivery medium but also as a participatory dialogue space that allows for an exchange of meaning between broadcasters and listeners. Interactive and educational communication patterns have been proven to increase adolescents' understanding and awareness of reproductive health issues. Thus, radio remains relevant as a credible and contextual public education medium for adolescents amidst the limitations of formal sex education.